Interactions of corporate governance players: Power, trust and audit quality / Fatimah Mat Yasin - Fatimah , Mat Yasin (2018)
A review of the literature has identified the importance of the interactions between key corporate governance players in enhancing audit quality. Nonetheless, little is known about how the interactions between the external auditor and other key governance players (i.e. audit committee and internal audit function) possibly influence the quality of audit performance. The aim of this study is to provide insights on the nature of the interactions between external auditor (EA) with the audit committee (AC) and internal audit function (IAF); and how these interactions influence audit quality. This study adopts an interpretive approach by using semi-structured interviews as the research method. Interviews were conducted with audit partners/senior managers, audit committee members and the head of the internal audit functions to provide insights to the research questions outlined in the study. While agency theory is an underlying theory that explains the subject under study, the study also draws on the power theory and source credibility theory to enhance understanding and illustrate the important roles of power and trust in the interaction between the EA with AC and IAF that affect audit quality. The study has identified the elements of positive expert and will in the power theory as having the greatest impact on the interaction between the EA with AC and IAF that affect the EAs’ conduct of the audit. Expert power such as knowledge, expertise and experience of AC and IAF which are combined with their willingness to exercise the power enable ACs and IAFs to actively influence the audit performance. The findings also show the importance of social interaction in characterising the nature of interactions between the key governance players. The social interaction assists in building rapport between the parties which allows for greater interactions and information exchange between them that facilitate conduct of audit. The study also highlights the considerable importance of interpersonal quality (i.e. honesty, humbleness, respect) in promoting regular communication and the ability to discuss accounting and auditing matters more openly. Both social interaction and good interpersonal quality were found to be essential in creating a good vibe between the parties thereby helping to establish trust in their interactions. Findings imply both power and trust are important in determining working relationship in terms of information exchange between EA with the other two governance players. Inherently, the information and knowledge shared by ACs and IAFs during the interactions may influence the EAs’ actions when conducting the audit. With the presence of power and trust in the interactions, the quality of the audit process can be enhanced, particularly through audit planning, risk assessments, evidence gathering, and the timeliness of the audit. Eventually, it can enhanced the financial reporting quality and more accurate audit opinion can be provided. The study is significant as it provides insights into the specific aspects of interactions which focus on the role of power and trust and their influence on the conduct of auditors during the audit process. The findings are of interest to practitioners and regulators on the potential measures that enhance governance practice as well as the audit quality. The findings provide signals to the practitioners and policy-makers on the specific requirements in appointing the ACs and IAFs to enhance the interaction between the EAs with ACs and IAFs and accordingly improve the audit quality.